Excess late mortality among long-term gastric cancer survivors following gastrectomy: a population-based cohort study - Fu, Yi; Li, Jian (Journal of Gastrointestinal Oncology; Vol 17, No 3 (June 29, 2026): Journal of Gastrointestinal Oncology, 2026)
Background: Long-term survival after gastrectomy for gastric cancer (GC) is increasingly common, yet comprehensive understanding of late mortality patterns remains limited. This study aimed to quantify excess late mortality and identify associated risk factors among long-term GC survivors.Methods: A retrospective cohort study was conducted using the Surveillance, Epidemiology, and End Results (SEER) data (1992–2022) including 8,637 long-term GC survivors after gastrectomy. Standardized mortality ratios (SMRs) and absolute excess risks (AERs) were calculated. Subgroup analyses were performed for all-cause, second malignant neoplasm (SMN)-related, and non-cancer health-related mortality. The relative-risk SMRs (RRSMRs) were estimated to assess effect modification by demographic and clinicopathological features.Results: The cohort experienced significantly elevated all-cause mortality [SMR =1.66, 95% confidence interval (CI): 1.61–1.70]. Non-cancer conditions became the predominant cause of late death (58.5%), surpassing recurrence (27.7%) and SMNs (11.7%). Younger age at diagnosis (15–49 years), radiotherapy, and chemotherapy were associated with particularly high excess mortality. Gastrointestinal diseases (SMR =2.30, 95% CI: 1.68–3.07) and infectious diseases (SMR =1.76, 95% CI: 1.53–2.00) showed the most pronounced elevations among non-cancer causes, while diabetes mortality risk was not significantly increased.Conclusions: Long-term GC survivors after gastrectomy face persistent excess mortality, primarily from non-cancer conditions. These findings highlight the need for risk-adapted survivorship care that extends beyond cancer surveillance to address late health risks in long-term GC survivors.